Diagnóstico de trastornos ruminales en bovinos en Guatumbamba, cantón Pujilí, provincia de Cotopaxi - Tulmo Negrete, Darwin Vinicio (2022)
In the Guatumbamba San Antonio area of Canton Pujilí, Province of Cotopaxi evaluates the state of different ruminal liquid samples that present physical and chemical alterations in terms of color, odor, viscosity, flotation, sedimentation, pH, activity, reduction protozoaria; in orina the percentage of eliminated ketones is valued; the variable variables are also influenced by the quality of the food, the state of the food, the volume of the food and the supplement, then the acidic state of the existing micro-environment in the rumen is affected; the allowed values are allowed to determine the existence of subacute ruminal acidosis in 75% of the vacations, as a consequence decreasing the lactation production is to find a minimum production of 11Lt and a maximum of 14Lt, corporate condition being 2.0 inferior and 3, 0 the mayor index, as a result of dicho trastorno ruminal; debit to its influence on the production of volatile acid acids and its absorption; to read the diagnostic with the results of the analysis is standardized with the methodology for determining ruminal alterations described by K. Petrovski, mediating the work of the camp using the tools at this level and also in the laboratory.